The Influence of Preschool Children's Intellectual Maturity and Thematic Learning on Physical Education Learning Outcomes in Elementary School - Raharja, Andri Tria; Wardhana, Kautsar Eka (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
This study was conducted to determine whether preschoolers' intellectual maturity affects the learning outcomes of physical education and health using a thematic learning method. The research method used in this study was a quasi-experiment, where the experimental group was given a thematic learning approach, while the control group was given a conventional learning approach. The sample used in this study consisted of 60 students, and a written test was used as the instrument at the end of the learning process. Analysis was conducted using a two-way analysis of variance (ANOVA) with a 2x2 factorial design. The results showed that the p-value for student maturity was 0.509, which is greater than the error rate of α (0.05), indicating that there is no difference in the influence of preschoolers' intellectual maturity on the learning outcomes of physical education and health. Meanwhile, the significance value of p (learning method) was 0.016, which is less than the error rate of α (0.05), indicating that there is an influence of the thematic learning approach on the learning outcomes of physical education and health. From these findings, it can be concluded that (a) there is no difference in the learning outcomes of physical education and health between students who are intellectually mature and those who are not, (b) there is a difference in the learning outcomes of physical education and health between students who are given a thematic learning approach and those who are given a conventional learning approach, and (c) there is an influence of preschoolers' intellectual maturity with the thematic learning method on the learning outcomes of physical education and health.